INTRODUCTION TO TIME SERIES AND FORECASTING - PETER J BROCKWELL; RICHARD A DAVIS (SWITZERLAND SPRINGER INTERNATIONAL, 2016)
Assuming a knowledge only of basic calculus, matrix algebra, and elementary statistics, this book places emphasis on methods and the analysis of data sets. It covers stationary processes, ARMA and ARIMA processes, multivariate time series and state-space models, and also has an optional chapter on spectral analysis.
Keywords: Time-Series Analysis -- Mathematical Statistics -- Probability-Theory